2004
DOI: 10.1007/s00432-004-0548-9
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor beta (ER?) is expressed in brain astrocytic tumors and declines with dedifferentiation of the neoplasm

Abstract: In as much as ERbeta is possibly the only ER expressed in astrocytes, its decreased expression may play an important role in astrocytic tumor initiation and in the potential response of glial neoplasms to tamoxifen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 33 publications
4
60
0
Order By: Relevance
“…[42][43][44] In the case of breast, colon and prostate cancer, as well as brain astrocytic tumors, ERb expression has been correlated to a higher tumor differentiation grade, in line with its antiproliferative and differentiating effects. [45][46][47][48] It is of interest that malignant lymphoid cells, as described for the cell lines used in this report, retain ERb expression. This may suggest that malignant transformation of cells of lymphoid origin is not generally associated with the loss of ERb expression and therefore remain as useful targets for therapy by ERb agonists.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] In the case of breast, colon and prostate cancer, as well as brain astrocytic tumors, ERb expression has been correlated to a higher tumor differentiation grade, in line with its antiproliferative and differentiating effects. [45][46][47][48] It is of interest that malignant lymphoid cells, as described for the cell lines used in this report, retain ERb expression. This may suggest that malignant transformation of cells of lymphoid origin is not generally associated with the loss of ERb expression and therefore remain as useful targets for therapy by ERb agonists.…”
Section: Discussionmentioning
confidence: 99%
“…However, findings from these studies have also shed light on pathways involved in the development and progression of glioma in humans. This research has drawn upon knowledge of the role of endogenous and exogenous sex steroids in the etiology and pathogenesis of breast cancer and endometrial cancer and from an understanding of the tissue-specific nature of steroid hormone action (34)(35)(36). For example, selective estrogen receptor modulators (SERMs) may function as either estrogen antagonists or agonists, depending on the target tissue and on the estrogen receptor (ER) subtype mediating a specific response (34).…”
Section: Clinical and Experimental Studiesmentioning
confidence: 99%
“…Several studies reported finding either no detectable ERs or progestin receptors or very low levels in human gliomas/glioblastoma (43-47), whereas glucocorticoid and/or androgen receptors were detected in a higher proportion of gliomas (43,46,47). However, several more recent studies have documented ER expression in a substantial proportion of gliomas, glioblastomas, and astrocytomas (25,35,36,49,52,53).…”
Section: Steroid Receptors In Normal Glial Cells and Glioma Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher incidence in men becomes evident around the age of female menarche, reaching a maximum around the age of menopause and diminishing thereafter (6). Progesterone, estrogen, and androgen receptors are expressed in meningiomas (7)(8)(9) and gliomas (10,11) in various degrees. Use of exogenous female sex hormones has been reported in relation to meningioma and glioma risk with inconsistent results (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%